The Influence of Investment, Energy Infrastructure, and Human Capital Towards Convergence of Regional Disparities in Sumatra Island, Indonesia; Using Oil and Gas Data and Without Oil and Gas - Hidayat, Muhammad; Bachtiar, Nasri; Sjafrizal, Sjafrizal; Primayesa, Elvina (International Journal of Energy Economics and Policy, 2023)
This study aims to analyze the level of economic disparity and the influence of several economic and social variables on the convergence process between regions on Sumatra Island by using oil & gas and non-oil data to support the achievement of the 10th goal of sustainable development or SDGs 2030. The dataset used is panel data totaling 154 Regencies/Cities from 2010-2020. The analytical tool used is the Theil index, conventional panel data regression approaches, panel spatial data, and comparisons with both approaches to produce the best model. The results of the Theil index show that the disparity trend is decreasing for both data. The disparity value of oil & gas is more remarkable than without oil & gas. Furthermore, comparing the panel data method produces a superior and realistic spatial model. From the spatial model using the SEM approach, the convergence speed for oil & gas is 4.01% with a half-life of about 17 years, and for non-oil & gas, it is 5.37% with a half-life of about 12 years. All variables significantly affect the convergence process and are valid for oil & gas and non-oil & gas data.